2018
DOI: 10.3390/ijms19123735
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis between a Resistant and a Susceptible Wild Tomato Accession in Response to Phytophthora parasitica

Abstract: Phytophthora parasitica is one of the most widespread Phytophthora species, which is known to cause multiple diseases in tomato and is capable of infecting almost all plant parts. Our current understanding of tomato-Phytophthora parasitica interaction is very limited and currently nothing is known at the whole genome or transcriptome level. In this study, we have analyzed and compared the transcriptome of a resistant and a susceptible wild tomato accession in response to P. parasitica infection using the RNA-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 47 publications
2
17
0
2
Order By: Relevance
“…ERF genes mainly mediate pathogen-and disease-related stimuli by integrating multiple signaling pathways, such as JA, ethylene ET, and SA pathways [36]. Besides, TFs in WRKY and MYB families are also involved in plant defense response to biotic stress, such as response to Phytophthora parasitica in tomato [37], resistance response to aphid in soybean and Chrysanthemum morifolium [18,38], and response to insect attack and bacterial infection in Arabidopsis thaliana [23].…”
Section: Discussionmentioning
confidence: 99%
“…ERF genes mainly mediate pathogen-and disease-related stimuli by integrating multiple signaling pathways, such as JA, ethylene ET, and SA pathways [36]. Besides, TFs in WRKY and MYB families are also involved in plant defense response to biotic stress, such as response to Phytophthora parasitica in tomato [37], resistance response to aphid in soybean and Chrysanthemum morifolium [18,38], and response to insect attack and bacterial infection in Arabidopsis thaliana [23].…”
Section: Discussionmentioning
confidence: 99%
“… 95 Phytophthora parasitica LA2093 (R) LA1581 (S) Leaves - Mitogen activated protein kinase (MAPK) signaling pathway; plant hormone signal transduction pathway (in both a susceptible and a resistant response). 94 Meloidogyne incognita M36 (R) Pusa Ruby (S) Moneymaker (S) Roots - Cell wall structure, development, primary and secondary metabolite, and defense signaling pathway (in a susceptible response). - Secondary metabolite and hormone-mediated defense responses (in a resistant response).…”
Section: Next-generation Sequencing Applied To Study Tomato-pathogen Interactionsmentioning
confidence: 99%
“…P. parasitica is mainly known as a root and fruit pathogen of tomato associated with Phytophthora root rot and buckeye rot diseases but leaf infection, stem canker, stem girdling, collar rot, blossom blight, and damping-off of seedlings have also been reported in tomatoes in different parts of the world 20 . To understand the molecular basis of resistance against P. parasitica , Azal Naveed and Ali 94 compared P. parasitica resistant and susceptible accessions of the wild relative tomato S. pimpinellifolium in response to infection. By comparing inoculated vs. control plants, these authors identified 2657 DEGs in the resistant accession and 3079 DEGs in the susceptible one.…”
Section: Next-generation Sequencing Applied To Study Tomato-pathogen Interactionsmentioning
confidence: 99%
“…References: 1, Song et al (2015) ; 2, NoĂŤl et al . (2007) ; 3, Lyu et al (2020) ; 4, Wu et al (2019) ; 5, GĂłngora-Castillo et al (2012) ; 6, Saiz-FernĂĄndez et al (2020) ; 7, Gupta et al (2017) ; 8, Klink et al (2007) ; 9, Berka et al (2020) ; 10, Molitor et al (2011) ; 11, Sharma Poudel et al (2019) ; 12, C. Zhang et al (2015) ; 13, Ye et al (2011) ; 14, HafrĂŠn et al (2010) ; 15, Caplan et al (2009) ; 16, HĂ˝skovĂĄ et al (2021b) ; 17, Crampton et al (2009) ; 18, Cerna et al (2017) ; 19, Coelho et al (2021) ; 20, Singh et al (2019) ; 21, Vitale et al (2014) ; 22, Naveed and Ali (2018) ; 23, Gorovits et al (2013) ; 24, Chen et al (2013) ; 25, Pan et al (2013) ; 26, Szajko et al (2020) ; 27, Guo et al (2021) ; 28, Yang et al (2017) ; 29, Paiva et al (2016) ; 30, Varela et al (2017) ; 31, Liu et al (2021) ; 32, Chen et al (2017) .…”
Section: Introductionmentioning
confidence: 99%